Silver linings of the COVID-19 lockdown in New Zealand - Jenkins, Matthew (PLoS One, 2021)
The COVID-19 pandemic has caused significant disruption, distress, and loss of life around the world. While negative health, economic, and social consequences are being extensively studied, there has been less research on the resilience and post-traumatic growth that people show in the face of adversity. We investigated New Zealanders’ experiences of benefit-finding during the COVID-19 pandemic and analysed qualitative responses to a survey examining mental well-being during the New Zealand lockdown. A total of 1175 of 2010 eligible participants responded to an open-ended question probing ‘silver linings’ (i.e., positive aspects) they may have experienced during this period. We analysed these qualitative responses using a thematic analysis approach. Two thirds of participants identified silver linings from the lockdown and we developed two overarching themes: Surviving (coping well, meeting basic needs, and maintaining health) and thriving (self-development, reflection, and growth). Assessing positive as well as negative consequences of the pandemic provides more nuanced insights into the impact that New Zealand’s response had on mental well-being.